2017
DOI: 10.1007/s00787-017-1048-1
|View full text |Cite
|
Sign up to set email alerts
|

Enrolment of children in psychosocial care: problems upon entry, care received, and outcomes achieved

Abstract: Psychosocial care systems have been designed so that specific problems are treated by specific care types. There is insufficient evidence as to which problem types are actually presented to the various care types. This study assessed types and severity of problems among children and adolescents upon enrolment in psychosocial care, compared to children not enrolled; also outcomes after 3 and 12 months, overall and per care type. We obtained data on a cohort of 1382 Dutch children aged 4–18 years (response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Overall, our findings suggest a properly functioning triage in the care system: first children and adolescents with longer trajectories experienced a lower rate of problem reduction and second after short treatment, problem reduction continued at follow‐up. These findings correspond with earlier research by Nanninga, Jansen, Knorth, and Reijneveld (), who found that the system of psychosocial care functions as intended regarding the distribution of type and severity of problems across care types (Nanninga et al., ). Overall, increased provision of care does thus not automatically lead to reduction of problems, and although overall psychosocial problems are reduced, a substantial subgroup has longer lasting problems.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our findings suggest a properly functioning triage in the care system: first children and adolescents with longer trajectories experienced a lower rate of problem reduction and second after short treatment, problem reduction continued at follow‐up. These findings correspond with earlier research by Nanninga, Jansen, Knorth, and Reijneveld (), who found that the system of psychosocial care functions as intended regarding the distribution of type and severity of problems across care types (Nanninga et al., ). Overall, increased provision of care does thus not automatically lead to reduction of problems, and although overall psychosocial problems are reduced, a substantial subgroup has longer lasting problems.…”
Section: Discussionsupporting
confidence: 91%
“…Psychosocial problems were assessed with the Dutch self-report and parent-report versions of the Strengths and Difficulties Questionnaire (SDQ) [ 25 – 28 ]. The SDQ consists of 25 items, measuring internalizing [Cronbach’s α parents = 0.78 (T1, T2, T3), adolescents = 0.75 (T1), 0.76 (T2), and 0.73 (T3)] and externalizing problems [Cronbach’s α parents = 0.83 (T1, T2, T3), adolescents = 0.74 (T1), 0.76 (T2), and 0.73 (T3)] [ 29 ]. The total difficulties score (TDS) ranges from 0 to 40, with higher scores indicating more problems.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of whether the barriers belong more to an institutional or individual/cultural type, they may prevent youth from getting diagnosed and treated in a timely and proper manner. This can happen even if services are organized and functioning as intended according to type and severity of problems [5].…”
Section: Responding To Fearmentioning
confidence: 99%